(untitled) (Global Journal of Management and Business Research, 2015)
This paper investigates the impact of defense burden on economic growth in Pakistan economy over the period 1980-2013. A three equations model is estimated through two stage least square (2SLS) method in order to investigate the direct and indirect impact of defense burden on economic growth. The findings of the model show that defense expenditure directly as well as indirectly retard economic growth in Pakistan.